Uncovering the role of wheat magnesium transporter family genes in abiotic responses - Tang, Yanhong; Yang, Xiaoyue; Li, Han; Shuai, Yating; Chen, Wang; Ma, Dongfang; Lü, Zhichuang (Frontiers in Plant Science, 2023)
The CorA / MGT / MRS2 family proteins are an important group of magnesium transporter proteins that maintain magnesium ion homeostasis in plant cells. To study MRS2/MGT genes in wheat, the physicochemical properties, chromosomal location, gene structure, cis-acting elements and duplication events of MGT family genes were conducted. A total of 24 MGT genes were identified on 18 chromosomes of wheat, with most of genes encoding hydrophilic proteins that are stable in nature. After functional domain analysis, only TaMGT1A, TaMGT1B, and TaMGT1D had GMN mutations to AMN, while all the other genes had conserved GMN tripeptide motifs. Phylogenetic analysis showed that the 24 TaMGT genes could be divided into four groups. Expression profiling showed that the TaMGT gene was differentially expressed under different stresses and at different growth and development stages. The expression levels of TaMGT4B and TaMGT4A were significantly up-regulated in cold damage. The expression level of TaMGT3B.3 was gradually increased with increasing time of Magnaporthe oryzae, indicating that TaMGT genes may have different functions. This study provides a theoretical basis for an in-depth investigation of the function of the TaMGT gene family in wheat.